The Native American heritage of the body-mind-spirit paradigm in osteopathic principles and practices. (September 2019) - Zegarra-Parodi, Rafael; Draper-Rodi, Jerry; Haxton, Jason; Cerritelli, Francesco
Abstract: The purpose of the current commentary was to document how Native American healing traditions may have influenced A.T. Still in the development of osteopathic principles and how current neuroscience models describing shamanic healing practices of Native American healers may have applicability for osteopathic manipulative practices. Recent materials from the Museum of Osteopathic Medicine document when Still was living among the Shawnee and suggest he was familiar with their healing traditions. Although he introduced the body-mind-spirit paradigm, derived from a key Native American healing concept, into Western medicine, this paradigm still lacks scientific grounding. Neuroscience models may offer a theoretical framework for the 'spiritual' component of the body-mind-spirit paradigm with brain predictive processing models that describe spiritual experiences of patients in altered states of consciousness. With its traditional medicine heritage and current evidence-based approach, the osteopathic profession is in a unique position to promote the scientific model of holistic care.